Value assessment of PD-1/PD-L1 inhibitors in the treatment of oesophageal and gastrointestinal cancers - Ou, Shun-Long; Luo, Jing; Wei, Hua; Qin, Xiao-Li; Jiang, Qian (Frontiers in Pharmacology, 2023)
Background: The efficacy and safety evidence of programmed cell death 1 (PD-1) and programmed death ligand-1 (PD-L1) checkpoint inhibitors in oesophageal cancer (EC), gastric cancer (GC) and colorectal cancer were inconsistent, obscuring their clinical application and decision making value. The aim of this study was to comprehensively evaluate the value of PD-1/PD-L1 inhibitors in EC, GC and colorectal cancer and assess the association between the value and cost of PD-1/PD-L1 inhibitors. Methods: A comprehensive search of trials of PD-1/PD-L1 inhibitors in EC, GC and colorectal cancer was performed in Chinese and English medical databases with a cut-off date of July 1, 2022. Two authors independently adopted the ASCO-VF and ESMO-MCBS to assess the value of PD-1/PD-L1 inhibitors. A receiver operating characteristic (ROC) curve was generated to establish the predictive value of the ASCO-VF score to meet the threshold of the ESMO-MCBS grade. Spearman’s correlation was used to calculate the relationship between the cost and value score or grade. Results: Twenty-three randomized controlled trials were identified: ten (43.48%) in EC, five (21.74%) in colorectal cancer, and eight (34.78%) in GC or gastroesophageal junction cancer (GEJC). For advanced diseases, ASCO-VF scores ranged from -12.5 to 69, with an average score of 26.5 (95% CI 18.4-34.6). Six (42.9%) therapeutic regimens met the ESMO-MCBS benefit threshold grade. The area under the ROC curve was 1.0 (P=0.002). ASCO-VF scores and incremental monthly cost were negatively correlated (Spearman’s ρ=-0.465, P=0.034). ESMO-MCBS grades and incremental monthly cost were negatively correlated (Spearman’s ρ=-0.211, P=0.489). Conclusion: There was no clinical benefit for PD-1/PD-L1 inhibitors in GC/GEJC. Pembrolizumab met valuable thresholds in the treatment of advanced microsatellite instability–high colorectal cancer. Camrelizumab and toripalimab were the PD-1/PD-L1 inhibitors with the most value for advanced EC.